BEYOND REASON: IQBAL’S INTERPLAY BETWEEN INTELLECT AND LOVE IN THE SEARCH FOR TRUTH - Khan, Shadab Ali (Sekolah Tinggi Agama Islam Sadra, 2025)
This paper delves into the profound and intricate relationship between Love (ishq) and Intellect (aql) within the philosophy of Muhammad Iqbal, a visionary poet and philosopher, aiming to reveal how these two forces shape the development of the human self (khudi) and contribute to the realization of spiritual and moral freedom. According to Iqbal, while intelligence is useful for getting to know things and thinking critically, love goes beyond reasoning and provides the spiritual and emotional depth needed to have a closer relationship with God. While both intellect and love are essential faculties of the human experience, Iqbal frames them as complementary forces in a dynamic relationship, where intellect is analytical, cautious, and calculating, whereas love is intuitive, passionate, and self-transcendent. The main motto of this research is to show how Iqbal emphasizes the primacy of love in the process of spiritual awakening, while affirming that both faculties work in tandem, without negating reason, but asserting that reason alone cannot lead to spiritual awakening or transformative action. For Iqbal, it is ishq that fuels the soul’s courage, sacrifice, and divine connection, ultimately leading to the strengthening of khudi. Through a comparative and analytical approach, the study highlights Iqbal’s integration of classical Islamic thought with modern existential concerns, demonstrating how love becomes a cosmic principle, whereas intellect remains a useful yet limited tool. In conclusion, this research asserts that true selfhood and moral leadership emerge not from intellect alone but rather through a harmonized interplay in which love leads, and intellect follows. This equilibrium lies at the heart of Iqbal’s vision for the revival of humanity.